2023
DOI: 10.1002/ptr.7941
|View full text |Cite
|
Sign up to set email alerts
|

Helichrysum stoechas (L.) Moench reduces body weight gain and modulates mood disorders via inhibition of silent information regulator 1 (SIRT1) by arzanol

Abstract: The prevalence of obesity is steadily rising, making safe and more efficient anti‐obesity treatments an urgent medical need. Growing evidence correlates obesity and comorbidities, including anxiety and depression, with the development of a low‐grade inflammation in peripheral and central tissues. We hypothesized that attenuating neuroinflammation might reduce weight gain and improve mood. We investigated the efficacy of a methanolic extract from Helichrysum stoechas (L.) Moench (HSE), well‐known for its anti‐i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…We also present evidence on the attenuation of mechanical allodynia on trauma-induced NP by the extract. It has been reported that chronic administration of plant-derived extracts is more effective than the single administration [ 32 , 47 ] and, in future studies, it will be worthwhile to investigate the efficacy of MOE after repeated treatment. MOE pain-relieving activity was devoid of any alteration in the animals’ gross behavior, and the extract did not produce any locomotor impairment.…”
Section: Discussionmentioning
confidence: 99%
“…We also present evidence on the attenuation of mechanical allodynia on trauma-induced NP by the extract. It has been reported that chronic administration of plant-derived extracts is more effective than the single administration [ 32 , 47 ] and, in future studies, it will be worthwhile to investigate the efficacy of MOE after repeated treatment. MOE pain-relieving activity was devoid of any alteration in the animals’ gross behavior, and the extract did not produce any locomotor impairment.…”
Section: Discussionmentioning
confidence: 99%